Assessing the reliability of the modified Gartland classification system for extension-type supracondylar humerus fractures. (2019) - Teo, T. L.; Schaeffer, E. K.; Habib, E.; Cherukupalli, A.; Cooper, A. P.; Aroojis, A.; Sankar, W. N.; Upasani, V. V.; Carsen, S.; Mulpuri, K.; Reilly, C.
Abstract: Purpose: The Gartland extension-type supracondylar humerus (SCH) fracture is the most common paediatric elbow fracture. Treatment options range from nonoperative treatment (taping or casting) to operative treatments (closed reduction and percutaneous pinning or open reduction). Classification variability between surgeons is a potential contributing factor to existing controversy over treatment options for type II SCH fractures. This study investigated levels of agreement in extension-type SCH fracture classification using the modified Gartland classification system. Methods: A retrospective review was conducted on 60 patients aged between two and 12 years who had sustained an extension-type SCH fracture and received operative or nonoperative treatment at a tertiary children's hospital. Baseline radiographs were provided, and surgeons were asked to classify the fractures as type I, IIA, IIB or III according to the modified Gartland classification. Respondents were then asked to complete a second round of classifications using reshuffled radiographs. Weighted kappa values were calculated to assess interobserver and intraobserver levels of agreement. Results: In all, 21 paediatric orthopaedic surgeons responded to the survey and 15 completed a second round of ratings. Interobserver agreement for classification based on the Gartland criteria between surgeons was substantial with a kappa of 0.679 (95% confidence interval (CI) 0.501 to 0.873). Intraobserver agreement was substantial with a kappa of 0.796, (95% CI 0.628 to 0.864) Conclusion: Radiographic classification of extension-type SCH fractures demonstrated substantial agreement both between and within surgeon raters. Therefore, classification variability may not be a major contributing factor to the treatment controversy for type II SCH fractures and treatment variability may be due to differences in surgeon preferences. Level of Evidence: III